Metal-organic framework-derived mesoporous B-doped CoO/Co@N-doped carbon hybrid 3D heterostructured interfaces with modulated cobalt oxidation states for alkaline water splitting - Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Kim, Tae Hyeong; Nam, Dong Hwan; BabaRao, Ravichandar; Lee, Seunghyun (Small, 2023)
Heteroatom-doped transition metal-oxides of high oxygen evolution reaction (OER) activities interfaced with metals of low hydrogen adsorption energy barrier for efficient hydrogen evolution reaction (HER) when uniformly embedded in a conductive nitrogen-doped carbon (NC) matrix, can mitigate the low-conductivity and high-agglomeration of metal-nanoparticles in carbon matrix and enhances their bifunctional activities. Thus, a 3D mesoporous heterostructure of boron (B)-doped cobalt-oxide/cobalt-metal nanohybrids embedded in NC and grown on a Ni foam substrate (B-CoO/Co@NC/NF) is developed as a binder-free bifunctional electrocatalyst for alkaline water-splitting via a post-synthetic modification of the metal-organic framework and subsequent annealing in different Ar/H-2 gas ratios. B-CoO/Co@NC/NF prepared using 10% H-2 gas (B-CoO/Co@NC/NF [10% H-2]) shows the lowest HER overpotential (196 mV) and B-CoO/Co@NC/NF (Ar), developed in Ar, shows an OER overpotential of 307 mV at 10 mA cm(-2) with excellent long-term durability for 100 h. The best anode and cathode electrocatalyst-based electrolyzer (B-CoO/Co@NC/NF (Ar)(+)//B-CoO/Co@NC/NF (10% H-2)(-)) generates a current density of 10 mA cm(-2) with only 1.62 V with long-term stability. Further, density functional theory investigations demonstrate the effect of B-doping on electronic structure and reaction mechanism of the electrocatalysts for optimal interaction with reaction intermediates for efficient alkaline water-splitting which corroborates the experimental results.
Keywords: 3D heterostructures; B-doped metal-oxides; electrocatalysts; hydrogen evolution reactions; metal-organic frameworks; oxygen evolution reactions

Metal-organic frameworks for enhanced hydrogen generation from syngas: a density functional theory approach - Gopalsamy, Karuppasamy; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; BabaRao, Ravichandar (CHEMPLUSCHEM, 2024)
Keywords: carbon capture; H-2 separation; Metal organic; Porous coordination network (PCN-250); Syngas